METAFORA KONSEPTUAL PADA WACANA RETORIKA POLITIK - Retno Purwani Sari; Tatan Tawami (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
Conceptual methaphors represent the way people think, speak and act. Inspite of their rhetorical function in literature, as an innovative language, they emerge as expressions to manifest every speaker’s experience. In political discourse, they are proposed to be an effective persuasive device to catch people’s attention and political elits. These metaphors are produced and being used so natural that they are treated as common expressions.The main issue is that the way in which metaphors are produced naturally.In response to the issue, the aim of this study is to describe the cognitive mechanism of conceptual metaphors, as a basis of linguistic metaphors. Emphirically, this study applied analytic descriptive qualitative method with reading and taking a note as techniques of collecting data – using distric election as data limitation. In analyzing data, classified data were analyzed using distributional technique of analytic descriptice. The result shows that conceptual metaphors in political discourse are interpreted as metaphors constructed through structural, orientational, and ontologis process.